2012
DOI: 10.1007/s12298-012-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced oxidative stress in the common bean legume, Phaseolus vulgaris L. seedlings and its amelioration by exogenous nitric oxide

Abstract: The adverse effects of arsenic (As) toxicity on seedling growth, root and shoot anatomy, chlorophyll and carotenoid contents, root oxidizability (RO), antioxidant enzyme activities, H 2 O 2 content, lipid peroxidation and electrolyte leakage (EL%) in common bean (Phaseolus vulgaris L.) were investigated. The role of exogenous nitric oxide (NO) in amelioration of As-induced inhibitory effect was also evaluated using sodium nitroprusside (100 μM SNP) as NO donor and 2-(4-carboxy-2-phenyl)-4,4,5,5-tetramethylimid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 43 publications
7
69
1
Order By: Relevance
“…Similar situation was also observed in salt-affected cereals, legumes and other vegetable crops [34,39,57,61,67]. Significant increase in MDA content and loss in photosynthetic apparatus have been recognized as the marks of oxidative stress in plants [5,6,10,39,57,64,68,69] and may be one of the prime reasons for NaCl-induced growth inhibition in the present material. It is also clear that oxidative damage at initial growth stages was effectively prevented in four genotypes by mitigating membrane damage at reproductive stage, but it was quite impossible for the PUSA-90-2 and WBK-CB-14 varieties to recover from NaCl-induced oxidative damage due to complete failure of antioxidant defense throughout the treatment period.…”
Section: ] and Phaseolus Aureussupporting
confidence: 82%
“…Similar situation was also observed in salt-affected cereals, legumes and other vegetable crops [34,39,57,61,67]. Significant increase in MDA content and loss in photosynthetic apparatus have been recognized as the marks of oxidative stress in plants [5,6,10,39,57,64,68,69] and may be one of the prime reasons for NaCl-induced growth inhibition in the present material. It is also clear that oxidative damage at initial growth stages was effectively prevented in four genotypes by mitigating membrane damage at reproductive stage, but it was quite impossible for the PUSA-90-2 and WBK-CB-14 varieties to recover from NaCl-induced oxidative damage due to complete failure of antioxidant defense throughout the treatment period.…”
Section: ] and Phaseolus Aureussupporting
confidence: 82%
“…5f). Previous studies also reported severe lipid peroxidation in different plant species under arsenic stress [56,58]. The increase in activity of these antioxidative enzymes and MDA content is quite obvious for the efficient recycling of ROS to ensure normal plant growth.…”
Section: Discussionmentioning
confidence: 85%
“…Most As and Cd appeared to be accumulated in roots and only a limited amount was translocated to the aboveground parts, suggesting their low mobility in both species. Greater capacity of a species to accumulate appreciable amounts of metal(loid)s in roots and their restricted transfer to the aerial tissue signifies its better ability to tolerate metal(loid) stress (Ishtiaq and Mahmood, 2011;Garg and Singla, 2012;Talukdar, 2013). Tiwari et al (2014) found enhanced expression of transporters (OsNRAMP1) in transgenic lines of rice, which might have contributed to considerable accumulation of Cd and As in roots.…”
Section: Discussionmentioning
confidence: 99%